Interactive and interactional metadiscourse markers in research articles of Indonesian expert writers - Kustyasari , Dian; Basthomi, Yazid; Anugerahwati, Mirjam (Universitas Muhammadiyah Sidoarjo, 2021)
Academic writing articles serve as the medium of communication among scholars to share knowledge and new inquiries and are made in such a way that the idea they deliver is both understandable and accepted. One essential action to accomplish this is by employing metadiscourse markers. Metadiscourse is viewed as an essential element of credible written texts created by students of ESL and native speakers, by which the intelligibility of communication in research articles can be accomplished through suitable discipline conscience, norms, and belief to track the writers’ pathway to academic promotions. Therefore, employing descriptive qualitative approach, this study aims at investigating the utilization of interpersonal metadiscourse markers and their functions in academic writing. Analysing discussion section of research articles written by Indonesian expert writers, the results show that the metadiscourse markers in the articles are found to be similar to the commonly used markers among academic community, including interactive and interactional markers. Moreover, the employment of markers in the articles reveal the functions of them to indicate relation between sentences, involvement of readers, existence of example, limitation of commitment to propositions, emphasis on general practice and certainty, and reference to the writer. HIGHLGHTS: The appropriate utilization of interactive and interactional metadiscourse markers in research articles indicates the international norm of academic writing. The Indonesian expert writer articles fulfill the intelligibility of communication in international research articles. The writing course in the universities needs to emphasize the essential functions of metadiscourse markers.